Transport of ethanol in baker's yeast - Kotyk, A; Alonso, A (Folia microbiologica, 1985)
Ethanol is transported into various strains of baker's yeast by simple diffusion (no effect of inhibitors and a linear concentration dependence of the initial rate of uptake and final distribution in cells). It distributes itself in 96.6 +/- 16.2% of intracellular water.
Keywords: biologický transport; Biological Transport; Ethanol; ethanol; Saccharomyces cerevisiae